Teacher Professionalism in the Modern Era: Perspectives of Students at Muhammadiyah University of Luwuk - Melda B. Dadang; Ratmi Awalta Ahmad; Lia Rahayu; Patmawati Yabu (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2026)
Teacher professionalism is a crucial factor in enhancing the quality of education amidst digital technological advancements and the changing characteristics of 21st-century learners. This study aims to examine the perspectives of students at Universitas Muhammadiyah Luwuk regarding the concept of modern teacher professionalism, including the essential competencies required for professional teachers and the various challenges faced in maintaining and sustaining high standards of professionalism.Using a descriptive quantitative approach, this research involved 50 students selected through a purposive sampling technique. Data were collected using Google Forms and analyzed descriptively through frequencies, percentages, and mean scores.The findings indicate that students hold a positive view of current teacher professionalism. The aspects achieving the highest mean scores were teacher creativity in the learning process ($M = 4.50$), discipline ($M = 4.48$), and continuous professional competency development ($M = 4.44$). Additionally, a majority of respondents identified creativity, tidiness/cleanliness, and the ability to master learning technologies as key indicators of teacher professionalism.The results show that teacher professionalism is understood as a integration of pedagogical, professional, social, and personal competencies, supported by the adaptability to technological developments. The main challenges identified include rapid technological advances, the rise of Artificial Intelligence (AI), and evolving student characteristics. Therefore, teachers must continuously enhance their professional and digital competencies to create innovative, high-quality learning experiences tailored to 21st-century educational demands..